The relationship between national cultural dimensions, maternal anxiety and depression, and national breastfeeding rates: An analysis of data from 122 countries - Rajkumar, Ravi Philip (Frontiers in Communication, 2023)
Breastfeeding is a natural and universal practice across countries and cultures. It is estimated that several thousand lives could be saved per year if optimal breastfeeding practices were adopted across countries. In addition, breastfeeding has numerous health, emotional and developmental benefits for both the mother and her infant. Despite widespread awareness of these benefits, rates of breastfeeding initiation and maintenance remain suboptimal, both in high- and in low- and middle-income countries. Unfavourable breastfeeding outcomes are related to several factors, including variations in cultural values and the occurrence of common mental disorders in women during pregnancy and in the postnatal period. However, the relative contributions of culture and mental health to variations in national breastfeeding rates have not been examined to date. In the current study, recent United Nations International Children’s Emergency Fund (UNICEF) data on lifetime breastfeeding rates is analyzed in two stages, to first explore and then confirm the impact of cultural values and maternal mental health status at a cross-national level. It was found that the estimated prevalence of both depression and anxiety disorders in women of childbearing age was negatively correlated with breastfeeding rates. Significant associations were also observed for the cultural dimensions of individualism-collectivism and masculinity-femininity. The association between anxiety disorders and breastfeeding outcomes remained significant in multivariate analysis incorporating demographic and health variables that could exert a confounding effect. These results suggest that both cultural values and the assessment and treatment of maternal mental illness should be components of any programme aimed at communicating the benefits of breastfeeding or at improving breastfeeding outcomes. The inclusion of these components could help promote the values of cultural sensitivity, inclusiveness and equity in breastfeeding from a global perspective.